Characteristics and outcomes of women using emergency medical services for third-trimester pregnancy-related problems in India: a prospective observational study - Jennifer A Newberry; Corey B Bills; Elizabeth A Pirrotta; Matthew C Strehlow; G V Ramana Rao; Hyeyoun (Elise) Min; Ann E Evensen; Lawrence Leeman; S V Mahadevan (BMJ Open)
Objectives Characterise the demographics, management and outcomes of obstetric patients transported by emergency medical services (EMS).Design Prospective observational study.Setting Five Indian states using a centralised EMS agency that transported 3.1 million pregnant women in 2014.Participants This study enrolled a convenience sample of 1684 women in third trimester of pregnancy calling with a ‘pregnancy-related’ problem for free-of-charge ambulance transport. Calls were deemed ‘pregnancy related’ if categorised by EMS dispatchers as ‘pregnancy’, ‘childbirth’, ‘miscarriage’ or ‘labour pains’. Interfacility transfers, patients absent on ambulance arrival and patients refusing care were excluded.Main outcome measures Emergency medical technician (EMT) interventions, method of delivery and death.Results The median age enrolled was 23 years (IQR 21–25). Women were primarily from rural or tribal areas (1550/1684 (92.0%)) and lower economic strata (1177/1684 (69.9%)). Time from initial call to hospital arrival was longer for rural/tribal compared with urban patients (66 min (IQR 51–84) vs 56 min (IQR 42–73), respectively, p<0.0001). EMTs assisted delivery in 44 women, delivering the placenta in 33/44 (75%), performing transabdominal uterine massage in 29/33 (87.9%) and administering oxytocin in none (0%). There were 1411 recorded deliveries. Most women delivered at a hospital (1212/1411 (85.9%)), however 126/1411 (8.9%) delivered at home following hospital discharge. Follow-up rates at 48 hours, 7 days and 42 days were 95.0%, 94.4% and 94.1%, respectively. Four women died, all within 48 hours. The caesarean section rate was 8.2% (116/1411). On multivariate regression analysis, women transported to private hospitals versus government primary health centres were less likely to deliver by caesarean section (OR 0.14 (0.05–0.43))Conclusions Pregnant women from vulnerable Indian populations use free-of-charge EMS for impending delivery, making it integral to the healthcare system. Future research and health system planning should focus on strengthening and expanding EMS as a component of emergency obstetric and newborn care (EmONC).